Prevention of Human Papillomavirus Infection. Beyond Cervical Cancer: A Brief Review - Medeiros, Rita (2020)
Human papillomavirus is responsible for almost all cases of cervical cancer, an important portion of anogenital and oropharyngeal invasive and preinvasive lesions, as well as genital warts (condyloma acuminatum) and recurrent respiratory papillomatosis. Currently, three prophylactic vaccines against high-risk Human papillomavirus are commercialized in many countries worldwide.